Psychological Distress and Protective Behaviors During the COVID-19 Pandemic Among Different Populations: Hong Kong General Population, Taiwan Healthcare Workers, and Taiwan Outpatients - Chung, Gary Ka-Ki; Strong, Carol; Chan, Yat-Hang; Chung, Roger Yat-Nork; Chen, Jung-Sheng; Lin, Yi-Hsuan; Huang, Ru-Yi; Lin, Chung-Ying; Ko, Nai-Ying (Frontiers in Medicine, 2022)
Purpose: The novel coronavirus disease 2019 (COVID-19) caused psychological distress and changed the human living styles. However, rarely have studies examined the psychological distress and protective behaviors across different populations. Therefore, the present study aimed to assess psychological distress, protective behaviors, and potential predictors on psychological distress and protective behaviors across Hong Kong general population, Taiwan healthcare workers, and Taiwan outpatients. Methods: A cross-sectional design was used to recruit participants from Hong Kong and Taiwan. Telephone interviews were carried out for Hong Kong participants (n=1067; 30.2% males); online surveys were used for Taiwan healthcare workers (n=500; 8.0% males) and Taiwan outpatients (n=192; 32.8% males). All the participants completed questions on psychological distress and protective behaviors. Multiple linear regressions and multivariable logistic regressions were employed to explore the potential predictors of psychological distress and protective behaviors, respectively. Results: Hong Kong participants had significantly lower levels of psychological distress than Taiwan participants (Mean [standard deviation; SD] = 0.16 [0.39] vs. 0.47 [0.59] in healthcare workers and 0.46 [0.65] in outpatients; p<0.001). Hong Kong participants (51.7%) and Taiwan outpatients had more people showing fear of COVID-19 (52.0%) than Taiwan healthcare providers (40.8%; p<0.001). Moreover, Hong Kong participants engaged the most in protective behaviors, followed by Taiwan healthcare providers and Taiwan outpatients (ps<0.001). Moreover, being a female, fear of COVID-19, and worried about personal savings were associated with protective behaviors in general. Conclusions: Despite the greater COVID-19 severity and fear of COVID-19 in Hong Kong, the general population in Hong Kong experienced less psychosocial distress with higher compliance to protective behaviors than the other groups in Taiwan.